Socio-Demographic Sheep Farmers’ Characteristic and Their Association with Forage Supply and Performance on Small Scale Farms In West Java - Kumalasari, Nur Rochmah; Rahayu, Annisa Ulfa; Srifani, Anifah; Setiana, Muhammad Agus (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2023)
The scale of improvement in sheep farmers productivity depends on many factors, such as farming system, forage management and human resources. The objectives of the research were (a) to determine the socio-demographic profiles of the sheep farmers in West Java and (b) to study associations with forage management practices and production outcomes parameters on their farms. The study was conducted on 90 sheep flocks in West Java Province in March 2019 to June 2021. Interviews of farmers were performed by using standardized questionnaires. Forage samples were collected from each farm for forage analysis. On each farm, all of the animals were measured at random and evaluated for body condition scoring (1-5, including half scores). All statistical data analyses were conducted using R version 4.1.0. Analysis of variance was used to test for differences in quantitative data, while the potential associations of the socio-demographic characteristics with the forage management practices and production outcomes were evaluated by a linear model. The result showed that the majority of animal farmers were male (92.3%) with the age of farmers was 48.75±9.28 years. The mean farming experience of farmers was 9.47±5.1 years with a few farmers (11.5%) working full-time in animal farming and over 50% had animal farming as a secondary activity. The research concluded that the most associated socio-demographic characteristic with the variables studied were farmers’ main occupation following with age, gender and education. Keywords sheep farmers, education, forage supply, management